2009
DOI: 10.1002/cncr.24724
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics associated with early and late melanoma metastases

Abstract: BACKGROUND: Differences in risk factors for metastases at different time intervals after treatment have been described in several malignancies; however, to the authors' knowledge, no extensive study examining this issue in melanoma has been conducted to date. METHODS: The authors performed a nested case-control study of patients with melanoma who presented with only local disease. Patients in the case group included 549 patients who developed metastases 6 months after surgery. Of these, 320 patients developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
22
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 14 publications
5
22
0
Order By: Relevance
“…Brauer et al compared 320 early recurrence patients (<3 year DFI) to 70 LR (>8 year DFI) and found thinner, non-ulcerated lesions and a relative absence of previous non-melanoma skin cancers in the late recurrence group, but could not confirm the significance of age or sex on multivariate analysis. 7 Our analysis would seem to unify the findings of these two prior, series in that age, gender, thickness and ulceration were all independently associated with late recurrence. While older patients may be less likely to develop late melanoma recurrences due to competing mortality risks, the mean age of the even the early recurrence cohort (51 years) would suggest that these patients would be likely to live well beyond 10 years, excluding their melanoma diagnosis.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Brauer et al compared 320 early recurrence patients (<3 year DFI) to 70 LR (>8 year DFI) and found thinner, non-ulcerated lesions and a relative absence of previous non-melanoma skin cancers in the late recurrence group, but could not confirm the significance of age or sex on multivariate analysis. 7 Our analysis would seem to unify the findings of these two prior, series in that age, gender, thickness and ulceration were all independently associated with late recurrence. While older patients may be less likely to develop late melanoma recurrences due to competing mortality risks, the mean age of the even the early recurrence cohort (51 years) would suggest that these patients would be likely to live well beyond 10 years, excluding their melanoma diagnosis.…”
Section: Discussionsupporting
confidence: 56%
“…As evidenced by the wide range of frequencies reported in prior series (0.41% to 25% (Table 3)) 1,7–22 , determination of the precise number is challenging. The variability may result from small sample size, inadequate long-term follow up, or referral bias.…”
Section: Discussionmentioning
confidence: 99%
“…The capacities in which the immune system can interact with melanomas are complex and can be different in different circumstances. Some authors have implicated components of the immune system such as macrophages as having a primarily pro-tumor and pro-metastasis function [250-253], while other authors have identified components of the immune system that can negatively regulate melanoma and melanoma metastasis [254]. Enhancement of immune-mediated tumor rejection is a central means by which promising new melanoma therapies function [255].…”
Section: Other Considerations In Melanoma Metastasismentioning
confidence: 99%
“…In a previous study of over 500 metastatic skin cancers, early metastasis (<3 years after surgery) was found to be significantly associated with past history of non-melanoma skin cancer, thicker lesions (Breslow depth), and ulcerative melanomas (19). In contrast, a history of non-ulcerative melanoma was found to be associated with late recurrence (>8 years after primary disease), this being consistent with our observation of tendency for orbital metastases of cutaneous melanoma to be a late phenomenon.…”
Section: Discussionmentioning
confidence: 88%